Experiencing the thirty years war : A brief history with documents - Medick, Hans; Marschke, Benjamin (Boston Bedford/St. Martin's, 2013)
Study the Thirty Years War from the perspective of those who lived it as Experiencing the Thirty Years War as an unprecedented collection of personal accounts come together to share the experience of early modern warfare.
Includes bibliographies and index
Keywords: Tham khảo